Efficacy and cost-effectiveness of nurse-led care involving education and engagement of patients and a treat-to-target urate-lowering strategy versus usual care for gout: a randomised controlled trial. Issue 10156 (20th October 2018) - Doherty, Michael; Jenkins, Wendy; Richardson, Helen; Sarmanova, Aliya; Abhishek, Abhishek; Ashton, Deborah; Barclay, Christine; Doherty, Sally; Duley, Lelia; Hatton, Rachael; Rees, Frances; Stevenson, Matthew; et al.
Summary: Background: In the UK, gout management is suboptimum, with only 40% of patients receiving urate-lowering therapy, usually without titration to achieve a target serum urate concentration. Nurses successfully manage many diseases in primary care. We compared nurse-led gout care to usual care led by general practitioners (GPs) for people in the community. Methods: Research nurses were trained in best practice management of gout, including providing individualised information and engaging patients in shared decision making. Adults who had experienced a gout flare in the previous 12 months were randomly assigned 1:1 to receive nurse-led care or continue with GP-led usual care. We assessed patients at baseline and after 1 and 2 years. The primary outcome was the percentage of participants who achieved serum urate concentrations less than 360 μmol/L (6 mg/dL) at 2 years. Secondary outcomes were flare frequency in year 2, presence of tophi, quality of life, and cost per quality-adjusted life-year (QALY) gained. Risk ratios (RRs) and 95% CIs were calculated based on intention to treat with multiple imputation. This study is registered withwww.ClinicalTrials.gov, numberNCT01477346 . Findings: 517 patients were enrolled, of whom 255 were assigned nurse-led care and 262 usual care. Nurse-led care was associated with high uptake of and adherence to urate-lowering therapy. More patients receiving nurse-led care had serum urate concentrations less than 360 μmol/L at 2 years than those receiving usual care (95% vs 30%, RR 3·18, 95% CI 2·42–4·18, p<0·0001). At 2 years all secondary outcomes favoured the nurse-led group. The cost per QALY gained for the nurse-led intervention was £5066 at 2 years. Interpretation: Nurse-led gout care is efficacious and cost-effective compared with usual care. Our findings illustrate the benefits of educating and engaging patients in gout management and reaffirm the importance of a treat-to-target urate-lowering treatment strategy to improve patient-centred outcomes. Funding: Arthritis Research UK.